Nation-wide trends in non-alcoholic steatohepatitis (NASH) in patients with and without diabetes between 2004-05 and 2014-15 in England - Carruthers,J; Bottle,R; Laverty,AA; Khan,SA; Millett,C; Vamos,EP (Diabetes Research and Clinical Practice, 2017)
AimsThere are no national studies evaluating the epidemiology of non-alcoholic steatohepatitis (NASH) in England. NASH is becoming an increasingly important health issue given the inexorable rise in obesity and diabetes. We evaluated the rates of NASH in people with and without diabetes from 2004–2005 to 2014–2015.MethodsWe identified cases of biopsy-proven NASH in people with and without diabetes in England over an eleven-year period using Hospital Episode Statistics. We estimated incidence rates for each year. Negative binomial regression models were fitted to test trends.ResultsOver the study period, people without diabetes recorded a 3% reduction in admission rates per year (incidence rate ratio (IRR) (95% CI) 0.97 (0.96–0.98), p < 0.001), whilst there was an increase in admission rates in people with diabetes (IRR (95% CI) 1.01 (1.00–1.02), p = 0.04). In people with diabetes, this upward trend was driven by people over 65 years (IRR (95% CI) 1.03 (1.02–1.04), p < 0.001) and men (IRR (95% CI) 1.01 (1.0–1.02), p = 0.03). Inpatient mortality declined for people with diabetes by 2% per year after adjusting for age, sex and year (IRR (95% CI) 0.98 (0.95–0.99), p = 0.03). The 2% decline per year in inpatient mortality for people without diabetes did not achieve statistical significance after adjustment (IRR (95% CI) 0.98 (0.95–1.01), p = 0.175).ConclusionsThere was a decline in NASH-related hospital admissions amongst people without diabetes over eleven years, whilst rates increased in people with diabetes. These observations highlight the increasing burden of NASH.